Prática espacial feminista como disrupção: o Coletivo Tereza de Benguela como embrião revolucionário - Renata Nogueira Morais Costa (2023)
This work proposes feminist spatial practice as a revolutionary potential in the face of current experience and spatial production, which are sexist and highlight the inequalities between the sexes in the city. In this way, a reflection of the asymmetric condition of women and men is developed based on the social roles of each sex. In addition, the research elaborates the critical possibilities of the constitution of spaces based on the denial of the heterogeneous and on the attempt to standardize territories and bodies. The bet of a confrontation with the sexist and unequal way of organization is revealed from the Tereza de Benguela Collective, as a feminist spatial practice. Based on this collective of maids from Belo Horizonte, the research intends to answer the question: “To what extent feminist spatial practice can be disruptive?”. Furthermore, the dissertation aims to: a) discuss a critical-spatial construction carried out through the experience of users and inhabitants, from a feminist perspective; and b) reveal the contributions that feminist theory offers to urban theory.